2020
DOI: 10.3390/min10050435
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Battery Scrap Recycling and Nickel Slag Cleaning with Methane Reduction

Abstract: Innovative recycling routes are needed to fulfill the increasing demand for battery raw materials to ensure sufficiency in the future. The integration of battery scrap recycling and nickel slag cleaning by reduction with methane was experimentally researched for the first time in this study. Industrial nickel slag from the direct Outotec nickel flash smelting (DON) process was mixed with both synthetic and industrial battery scrap. The end products of the slag-scrap mixtures after reduction at 1400 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 44 publications
7
31
1
Order By: Relevance
“…Figure 1 shows a flowchart of the proposed process investigated in this article. In previous studies by the authors, the integration of battery recycling to nickel slag cleaning was reported successful for the first time [24]. Unlike these previous studies and many industrial pyrometallurgical processes for battery recycling, this approach emphasizes the importance of mechanical pre-treatment to minimize the loss of valuable metals to the slag.…”
Section: Introductionmentioning
confidence: 97%
“…Figure 1 shows a flowchart of the proposed process investigated in this article. In previous studies by the authors, the integration of battery recycling to nickel slag cleaning was reported successful for the first time [24]. Unlike these previous studies and many industrial pyrometallurgical processes for battery recycling, this approach emphasizes the importance of mechanical pre-treatment to minimize the loss of valuable metals to the slag.…”
Section: Introductionmentioning
confidence: 97%
“…Although lithium does not represent a critical metal, its recovery, especially regarding future battery systems, where lithium will be manifested as an indispensable cathode component, becomes essential. In the field of battery recycling, research projects have been carried out for several years dealing with both single and combined mechanical, pyrometallurgical and hydrometallurgical processes as well as pyrolysis to recover battery components [5,10,11,[13][14][15][16][17][18][19][20][21][22][23]. However, the focus is set mainly on critical and valuable metals, which is the reason why lithium as a component has not been sufficiently considered [24].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, lithium was newly included among the European Union (EU)'s critical raw materials, which made its recovery, especially in the battery systems, where lithium is an indispensable cathode component, essential [13]. In the field of battery recycling, research projects have been carried out for several years dealing with both single and combined mechanical, pyrometallurgical, and hydrometallurgical processes as well as pyrolysis to recover battery components [5,10,11,[14][15][16][17][18][19][20][21][22][23][24]. However, the focus is mainly set on more valuable metals, which is the reason why lithium as a component has not been sufficiently considered [25].…”
Section: Introductionmentioning
confidence: 99%